An analysis on the development of elite sports policy in Taiwan: an institutional and Advocacy Coalition Framework perspective - Sheng-Hsiang Chen (2015)
Drawing upon a series of interviews with politicians, sports administrators, coaches, journalists and academics and with analysis based on the Advocacy Coalition Framework (ACF), this thesis examines elite sports development policy in Taiwan within a political context. It investigates the issues of whether or not sports development and policy-making reflect institutional features, and how sports policy has changed over time in Taiwan. It further explores the development systems of baseball, taekwondo and tennis, with a particular focus on similarities and differences between them at the elite level. Empirical data gathered from semi-structured interviews and documentary materials is analysed using an institutional approach together the ACF. The main findings suggest that, in essence, sports development and policy-making in Taiwan comply with institutional features and, during different periods from 1949 to the present day, have consistently been influenced by the political needs of the time. The analysis of the development systems of the three selected sports identified some major similarities. The government promotes them using a top-down approach and each sport relies heavily on the public funding. There sports have no national level facilities. Talent identification and development mainly occur in schools and are conducted through the competition systems. There is government financial support for elite athletes to participate in international events or for the governing bodies to host international events. The development systems for coaches share the same mechanisms. Finally, national athletes in each sport can enjoy sports science support from the government during squad training and international events. However, the case studies also reveal considerable differences. The governing bodies of taekwondo and tennis play a more dominant in elite development than that of baseball. Parents play a more significant role in the identification and development of tennis players than for the other sports. Only taekwondo national competitors train relatively frequently at the national training centre. The facilities for elite baseball players are more adequate than for the other sports. Elite baseball players enjoy the most international competition opportunities and taekwondo competitors the least. The existence of a professional baseball league and a highly professionalised international competition system for tennis serve to highlight the difference between the three sports in terms of the emergence of full-time athletes. In sum, this demonstrates quite clearly that there exists in Taiwan a single spine of sports development in general, but with variations.